Building Disaster Resilient Tourism through Strengthening Disaster Management Strategies in Batu City - Editha Praditya; Yusuf Ali; Surachman Surjaatmadja; Rui Duarte; Firre An Suprapto; Herlina Juni Risma Saragih (The Republic of Indonesia Defense University, 2023)
Indonesia has a high intensity of disaster events. The high incidence of disasters in Indonesia has had a detrimental impact on several sectors, one of which is the tourism sector. This study was conducted to find out actors who play a role in disaster management strategy and their relation to national defense. This study used QGIS software, MICMAC, and MACTOR for analysis. MICMAC analysis emphasizes factors or variables, and then MACTOR emphasizes actors. This research found that the institutional capacity between institutions in Batu City was good, but still needed to be improved. The role of actors in improving disaster management in tourism areas in Batu City is very crucial, especially BPBD and DLH as actors who influence other actors on strategy and disaster management in Batu City. The role of actors in disaster management through risk mapping, preparing emergency response plans, and involving the community in prevention efforts are important actions in disaster management. The success of these efforts will contribute to overall national security and stability. This condition led to the involvement of the Indonesian National Armed Forces (TNI) in emergency disaster response operations.